2015
DOI: 10.1017/s1751731115001226
|View full text |Cite
|
Sign up to set email alerts
|

Developmental competence of different quality bovine oocytes retrieved through ovum pick-up following in vitro maturation and fertilization

Abstract: In the present study, oocytes retrieved from cross bred Karan Fries cows by ovum pick-up technique were graded into Group 1 and Group 2, based on the morphological appearance of the individual cumulus-oocyte complexes (COCs). To analyze whether the developmental potential of the COCs bears a relation to morphological appearance, relative expression of a panel of genes associated with; (a) cumulus-oocyte interaction (Cx43, Cx37, GDF9 and BMP15), (b) fertilization ( ZP2 and ZP3), (c) embryonic development ( HSF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…R. M. Ferreira et al () reported the lower expression of genes associated with mitochondria (NRF1, POLG, POLG2, PPARGC1A, and TFAM), apoptosis (BAX and ITM2B), and oocyte maturation (FGF16, BMP15, and GDF9) due to heat stress and peak lactation. Besides, Saini et al () reported the lower expression of gene BMP15 and GDF9 in low‐quality oocytes recovered from living donors. We also observed (data not showed) that hatched Day 7.5 blastocysts were only produced when COCs from dairy cattle were maturated with BMP15 what probably indicates an improved oocyte competence.…”
Section: Discussionmentioning
confidence: 99%
“…R. M. Ferreira et al () reported the lower expression of genes associated with mitochondria (NRF1, POLG, POLG2, PPARGC1A, and TFAM), apoptosis (BAX and ITM2B), and oocyte maturation (FGF16, BMP15, and GDF9) due to heat stress and peak lactation. Besides, Saini et al () reported the lower expression of gene BMP15 and GDF9 in low‐quality oocytes recovered from living donors. We also observed (data not showed) that hatched Day 7.5 blastocysts were only produced when COCs from dairy cattle were maturated with BMP15 what probably indicates an improved oocyte competence.…”
Section: Discussionmentioning
confidence: 99%
“…CTSB activity is significantly increased in poor morphological quality oocytes and embryos when compared to those with good quality [ 14 , 19 ]. Given that OPU-derived oocytes have a relatively poor quality with high rates of apoptosis [ 13 , 18 ], it is plausible that E-64 enhanced the developmental rate and the quality of bovine COCs by regulating the apoptotic pathway ( Figure 4 ). A limitation of this study is that we used once-weekly OPU protocol that can allow for the development of dominant follicles which might affect the quality and stimulate apoptosis in oocytes within subordinate follicles.…”
Section: Resultsmentioning
confidence: 99%
“…Apoptosis is considered one of the causes of impaired developmental competence of mammalian COCs [ 14 , 15 , 16 , 17 ]. Poor quality OPU-derived COCs have higher rates of apoptosis when compared to good quality COCs [ 18 ]. We previously demonstrated that cathepsin B (CTSB) apoptotic pathway is a marker of inferior quality COCs and inversely correlated with the developmental competence of bovine COCs and preimplantation embryos (day 2, 4, and 7 embryos) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of the human literature for potential CC candidate mRNA biomarkers was performed [10], and genes were selected based on their functions. In some cases, the genes selected were based on data in non-human animals [18][19][20][21][22][23][24]. Gene products associated with oocyte maturation included calmodulin 1 (CALM1), gap junction alpha-4 protein (GJA4), gremlin (GREM1), and inhibitor of growth protein 1 (ING1).…”
Section: Introductionmentioning
confidence: 99%